With love and laughter, John Ritter - Yasbeck, Amy, 1962- (Gallery Books, 2010)
The widow of John Ritter celebrates the life of her beloved late husband, discusses his untimely death, and shares how she and her family are dealing with their grief and loss of a husband and father.